THE EFFECT OF HEALTH WORKERS' COMPETENCY AND BRAND IMAGE ON OUTPATIENT PATIENTS' REVISIT INTEREST MEDIATED BY PATIENT TRUST IN RHC CLINIC - Only Pricilia; Hery Winoto Tj; Fushen (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
Quality health services are a major factor in improving community welfare. However, in the face of increasingly tight competition, RHC Clinic faces challenges in maintaining patient repeat visit interest. This study aims to analyze the effect of health worker competence and brand image on patient repeat visit interest, both directly and through the mediation variable of patient trust. The research method used is quantitative with the Structural Equation Model (SEM) approach through the WrapPLS 8.0 tool. Data were obtained from 100 respondents who were RHC Clinic patients. The results of the study showed that health worker competence and brand image had a significant positive effect on patient trust, which ultimately increased patient repeat visit interest. Patient trust proved to be a mediating variable that strengthened the relationship between health worker competence and brand image on repeat visit interest. Thus, RHC Clinic needs to improve the quality of health workers through routine training and strengthen brand image through marketing strategies and better services in order to maintain patient loyalty.